SISTEM PEMANTAUAN TANAMAN SAYUR DENGAN MEDIA TANAM HIDROPONIK MENGGUNAKAN ARDUINO - Zettry Buana; Oriza Candra; Elfizon Elfizon (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
Hydroponics is a method of farming or cultivating plants without using soil, but using farming technology that uses water, nutrients, and oxygen. The use of hydroponic systems has advantages such as the quantity and quality of higher and cleaner production, more efficient use of fertilizers and water, and easier control of pests and diseases. However, this system has disadvantages, namely, hydroponics is very in need of thoroughness, diligence, and regular monitoring. On the growth of hydroponic plants can be influenced by various factors, one of which is pH. This final project aims to create a monitoring system and stabilize the pH level of water in vegetable plants of mustard pakcoy, lettuce and red spinach in hydroponic growing media using Arduino microcontrollers on sensor networks. This tool consists of input received through a pH sensor and output in the form of a pH UP pump and a DOWN pH then ESP8266 as the data sender. The working principle of this tool is when the data used in this study is in the form of data obtained from sensors. Then the microcontroller will receive data from the sensor network, where the data is the amount of acidity / alkaline water in the scope of the plant. Then the microcontroller will send the data with the help of ESP8266 into the server that has been provided. The data sent from the microcontroller is in the form of acidity / alkaline water data, in the scope of the plant. The results of the Final Project testing and experiments have been going well. The pH sensor can detect acidity / base on water well and the components in the Final Project have also been going well.